Modelování provozních stavů a využitelnost elektrického generátoru navrženého pro spinningové kolo. - Sádlík, Jiří (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2013)
Diplomová práce provádí kompletní návrh generátoru do spinningového kola. Je řešena problematika současného vývoje a proveden analytický návrh generátoru. Pro analýzu a optimalizaci je používán program Maxwell. Na základě získaných výsledků je vytvořen model a konstrukční výkres generátoru. Závěr práce se věnuje problematice zapojení generátoru do elektrické sítě a cenové kalkulaci návratnosti investice.

This thesis provides complete design of generator into a spinning bike. The issue of current development is solved and the analytical design of the generator is made. The software Maxwell is being used for the analysis and optimization. On the basis of the obtained results is designed a model and a design drawing of the generator. The end of the thesis deals with the issue of connecting the generator to the mains supply and price calculation of the investment return.
Design, simulation and usability of the electric machine designed for the spinning bicycle
Keywords: Spinning; generátor; Maxwell; RMxprt; analyticky návrh; synchronní stroj; vinutí; připojení do elektrické soustavy; cenová kalkulace; návratnost investice; Spinning; generator; Maxwell; Rmxprt; analytical design; synchronous machine; winding; connection to the electricity grid; price calculation; return on investment.